The Role of The Teacher in Teaching Process - Taryanikova M.A (Genius Journals, 2021)
Teachers play a vital role in the implementation of the education plans at educational level. This role is sometimes challenged by the level of teachers’ efficiency in work performance where the educational resources are scarce. Teachers face challenges of the optimal use of the available resources in the production of maximum output. Realization of educational work in educational institutions is a complex activity. The difficulties of achieving educational work stand in the fact that education is a category that refers to human - individuals. Starting from the fact that each individual has its own peculiarities which differ from one another then, the educational approach is different for everyone and is implemented differently. The teacher is the one who has the leading role in the realization of educational work.
Keywords: Teaching processes; teachers; strategies; role of teachers